Platform for controlling and getting data from network connected drones in indoor environments - Arenal Pereira, Adrián; Pascual-Espada, Jordán; González-Crespo, Rubén; Rios-Aguilar, Sergio (Future Generation Computer Systems, 2018)
Nowadays drones can be used to complete a wide range of different tasks, like patrol, transportation and data collection. Many of these tasks are developed in indoor environments, like industrial premises, factories and buildings. This research work proposes a novel platform to manage drones in indoor environments. The proposed platform raises to manage drones like an internet of connected devices with sensors and actuators. This platform is based on a network of connected drones which communicates with a central server. Drones can be managed by users using a web application. The application allows to define flight plans and to get the drone sensor‘s data. Drones are connected to the server using a Wi-Fi network, they exchange constantly UDP messages. Using this platform users can design flight plans using an interactive map. Flight plans can be saved and sent to a connected Drone. This platform allows users to manage drones as connected objects, running flight plans and visualizing drones’ sensor data in real time. The proposal also can be adapted to many specific industrial uses, including new sensors in the drone like, gas, temperature, radiation, etc. or some actuators like grippers or dispensers.
Keywords: internet of things; connected drone; web services; drones; sensors; internet of drones; indoor flight planner; Scopus; JCR